Teachers’ Views in the Prefecture of Rethymno Regarding Ways of Addressing School Bullying Among Students - Χατζάκης, Στέργιος (Education Sciences, 2025)
The present study explores teachers' views on approaches to addressing school bullying of students. Using purposive sampling, four public school teachers from the Rethymno Prefecture were selected. Semi-structured interviews were conducted, transcribed, and analyzed through thematic analysis. Four main thematic categories emerged from the data analysis, reflecting teachers' views on strategies for addressing bullying: (a) at the individual level for the victim, (b) at the individual level for the perpetrator, (c) at the classroom level, and (d) at the whole-school level. The findings of the present study contribute to the further understanding of school bullying among school-aged children in Greece.